Effect of linewidth enhancement factor (LEF) on routes to chaos in optically injected semiconductor lasers - Al-Hosiny, N. M. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2021)
The effect of the linewidth enhancement factor (LEF) or α-factor on two common routes to chaos (mainly period-doubling and quasi-periodic routes) in optically injected semiconductor laser is theoretically investigated using bifurcation diagrams. The value of the LEF is slightly modified to examine the sensitivity of routes to chaos to any variation in the LEF. Despite the fact that LEF enhances chaos in the system, both routes are found to be highly insensitive to the variation in the LEF.
Optica Applicata, Vol. 51, 2021, nr 4, s. 621-632
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; injection locking; chaos; linewidth enhancement factor; routes to chaos